Intercropping of Indian mustard (Brassica juncea) with barley (Hordeum vulgare), rocket salad (Eruca sativa) and linseed (Linum usitatissimum) under limited irrigation conditions in reclaimed ravine land of river Yamuna - NARAYAN, D; PRAKASH, OM; BHUSHAN, L S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter season (rabi) of 1990-91 to 1992-93 in reclaimed ravine landof river Yamuna at Agra to study the effect of intercropping Indian mustard [Brassica juncea (L.) Czemj. & Cosson]with barley (Hordeum vulgare L.), rocket salad (Eruca sativa Mill.) and linseed (Linum lIsitatissimum L.) on yield,water-use efficiency, competition indices and monetary returns under limited irrigation conditions. Indian mustardbasedintercropping systems were found more productive than sole cropping of Indian mustard. Indian mustard +linseed intercropping system recorded the highest Indian mustard equivalent yield (1 995 kg/ha), water-use efficiency(10.31 kg/ha-mm), land-equivalent ratio (1.63) and monetary returns (Rs 17 982/ha), whereas Indian mustard + barleyintercropping system recorded the lowest yield, water-use efficiency, land-equivalent ratio and retums. Barley androcket salad were found dominant and linseed domina,ted as judged by the values of relative crowding coefficient andaggressivity. The yield of crops progressively increased with !lumber of irrigation and the average increase was 33 and58% with I and 2 irrigation respectively. However, water-use efficiency decreased by 11% with 1 irrigation and 21 %with 2 irrigation. The monetary returns increased with increasing levels of irrigation.